Occurrence of Pulvinaria flavescens brethes 1918 (Homoptera: Coccidae) on Citrus reticulata blanco in Brasília, DF - Kitayama, Kiniti (Pesquisa Agropecuaria Brasileira, 1993)
Pulvinaria flavescens, has been considered a pest of citrus in the Southern and Southeastern states of Brazil. This insect was detected in Brasília in 1985 in an orchard where competition of rootstocks of Citrus reticulata has been evaluated. The following parameters were evaluated: A. resistance of rootstocks to P. flavescens; B. leaf area reduction caused by the insect attack; C. possible place where the attack began; D. the mortality of P. flavescens caused by predators and parasitoids. At least, one rootstock (CV), based on proportion and on the average number of attacked leaves, could be considered resistant to the P. flavescens. Southern bord of the orchard facing the cerrado seems to be the place where de attack began. Mortality of up to 65% of P. flavescens could be credited to predators and parasitoids.